A rotary spinneret for high output of electrospun fibers with bimodal distribution. (5th October 2021) - Quan, Zhenzhen; Wang, Yihan; Zu, Yao; Qin, Xiaohong; Yu, Jianyong
Graphical abstract: Highlights: A novel rotary electrospinning spinneret is introduced. Bimodal distribution sub-micro fiber yield can be easily optimized by using quadratic general rotary unitized design. The correlation between fiber morphology and process parameters is analyzed. Rotary electrospinning spinneret is a cost-effective method for high throughput manufacturing of bimodal distribution sub-micro fibers. Abstract: Needleless electrospinning technology is an effective method for preparing large-scale nanofibers. In the present work, we developed a multi-hole curved surface rotary spinneret to fabricate sub-micro fibrous membrane with bimodal distribution structure. First, a finite element method was adopted to investigate electric potential and electric field strength of the spinneret; the formation of coarser and finer jets has been explained from the perspective of electric field. Then, the effects of solution concentration, applied voltage and spinneret rotation speed on the bimodal distribution fibers yield were optimized via quadratic general rotary unitized design (QGRUD). Lastly, the fiber diameter distribution and the mechanical properties of sub-micro fibrous membranes were characterized. The results suggested that the bimodal distribution sub-micro fibrous membranes exhibited excellent breaking strength and tensile modulus. This novel multi-hole curved surface rotary spinneret is promising for the high-output fabrication of sub-micro fibers with bimodal distribution.